Global trends and research hotspots of EAT-Lancet diet: a bibliometric analysis - Lin, Xiaoxiao; Wang, Shuai; Gao, Yue (Frontiers in Nutrition, 2024)
The EAT-Lancet diet is a groundbreaking and comprehensive dietary framework that has garnered significant attention in the fields of nutrition, sustainability, and public health. We aimed to conduct a bibliometric study to investigate current status and hotspots in the field of EAT-Lancet diet based on the Web of Science Core Collection (WOSCC) database, and the documents of EAT-Lancet diet published from Jan 1, 2019 to Sep 1.2023 were extracted. The bibliometric and visualized analysis were performed by VOSviewer 1.6.16 and WOSCC Online Analysis Platform. In total, 155 documents from 62 journals were included, and 735 authors from 389 institutions and 53 countries/regions contributed to the field of EAT-Lancet diet. The most productive countries/regions, institutions, authors, and journals were the USA, Wageningen University & Research, Johan Rockström, and Nutrients, respectively. The first highcited document was published in Lancet and authored by Willett et al in 2019. This is also the first study about EAT-Lancet diet. The article firstly proposed the "EAT-Lancet Diet" emphasizing balanced, plant-based eating to improve human health while addressing environmental concerns. In conclusion, in the field of EAT-Lancet diet, the main research hotspots and frontiers are the adaptation of EAT-Lancet diet, the composition of EAT-Lancet diet, and the benefits of EAT-Lancet diet for human health. The number of research on the EAT-Lancet diet is currently limited. There is a pressing need for further studies to broaden our understanding of the EAT-Lancet diet and its potential to enhance human health.